2019
DOI: 10.1021/acs.energyfuels.8b04307
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Tetraethylenepentamine-Impregnated Silica Sorbents for CO2 Capture

Abstract: The stability of silica impregnated with commercial tetraethylenepentamine (TEPA) under accelerated oxidizing conditions was evaluated, and the changes in the composition of sorbents during oxidative degradation were first reported. The oxidative stability of sorbents depended on the TEPA loading, oxidation duration, temperature, and O2 concentration. The marked loss of the CO2 adsorption capacity of the sorbents in O2-containing environments was mainly caused by changes in the functional groups of TEPA and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…49−51 Typically, the oxidation of the amine polymers 52 produces less basic imine, amide, and other species, which are less effective CO 2 sorbents. Amine oxidation in solid sorbents has been widely studied by Sayari, 53−56 Jones, 57,58 and others, 51,59,60 with oxidation mitigation strategies including design of more oxidation-resistant sorbents 30,31,58,61,62 as well as adding stabilizers to the amine formulations. 46,59 For example, Min et al have used 1,2-epoxybutane and found that the PEI/SiO 2 composite retained about 92% of its working capacity after exposure in an O 2containing simulated flue gas (15% CO 2 ) mixture for 30 days at 110 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…49−51 Typically, the oxidation of the amine polymers 52 produces less basic imine, amide, and other species, which are less effective CO 2 sorbents. Amine oxidation in solid sorbents has been widely studied by Sayari, 53−56 Jones, 57,58 and others, 51,59,60 with oxidation mitigation strategies including design of more oxidation-resistant sorbents 30,31,58,61,62 as well as adding stabilizers to the amine formulations. 46,59 For example, Min et al have used 1,2-epoxybutane and found that the PEI/SiO 2 composite retained about 92% of its working capacity after exposure in an O 2containing simulated flue gas (15% CO 2 ) mixture for 30 days at 110 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, physical aging and oxidation are two factors that can drastically impact the physical properties and functionality of any polymeric materials. Typically, the oxidation of the amine polymers produces less basic imine, amide, and other species, which are less effective CO 2 sorbents. Amine oxidation in solid sorbents has been widely studied by Sayari, Jones, , and others, ,, with oxidation mitigation strategies including design of more oxidation-resistant sorbents ,,,, as well as adding stabilizers to the amine formulations. , For example, Min et al have used 1,2-epoxybutane and found that the PEI/SiO 2 composite retained about 92% of its working capacity after exposure in an O 2 -containing simulated flue gas (15% CO 2 ) mixture for 30 days at 110 °C . Srikanth and Chuang studied TEPA/SBA-15 composites and found that addition of poly­(ethylene glycol) (200 or 600 Da) improved the adsorption performance of the sorbents and the oxidative degradation resistance .…”
Section: Introductionmentioning
confidence: 99%
“…An increase in intensity in the region 3200-3600 cm À 1 can be attributed to OH and NÀ H stretching vibrations for amine-treated sample. [20] In addition, the NÀ H group on carbon surface was confirmed by the presence of peaks at 1610 to 1620 cm À 1 and 1175 to 1375 cm À 1 for TEPA-anchored carbon. [30] Raman spectrum is suitable for identifying the changes in structural morphology on carbon surfaces.…”
Section: Characterization Of Surface-modified Carbonmentioning
confidence: 93%
“…[18,19] The stability of amine is a significant factor in creating an effective adsorbent. [20] The AC containing enriched nitrogen on its surface enhances their basic nature [21] and increases CO 2 adsorption capacities. [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Amine-containing solid adsorbents have been investigated for capturing CO 2 in dilute streams because of their strong CO 2 chemisorption capability, which enables high CO 2 /N 2 selectivity. These materials are prepared by immobilizing amines within porous inorganic matrices via surface grafting or impregnation methods. Such adsorbents can be degraded via various pathways, and, in particular, oxidative degradation of amines is the biggest challenge in their commercial implementation. Various studies were carried out to improve the oxidative stability of amine-containing adsorbents.…”
Section: Introductionmentioning
confidence: 99%